Zasada wzbudzania zaufania do państwa a autorytatywne rozwiązania w zakresie dostępu do broni palnej - Mikowski, Rafał (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The text presents the multidirectional inﬂ uence of the ways of exercising power and relations between public authorities and citizens in the context of common values, which are public order and security, against the background of the rules governing access to ﬁrearms. The shaping of the government’s policy in the ﬁeld of access to ﬁrearms is in many places marked by legal solutions characteristic of the remnants of the authoritarian regime. In terms of access to ﬁ rearms, the authoritarian manner of exercising power was characterized by the pursuit of strict control over gun ownership. The trust of the authoritarian authorities in certain social groups, limited to the minimum, was visible in the discretionary, but also planned and imperative exclusion of ﬁrearms from public life and reserving this right for services, organizations, or speciﬁc groups favorable to the authorities. The current regulations on the possession of ﬁrearms, both in Poland and in the world, show that the liberal policy of administering access to ﬁrearms is based on democratic solutions. The policy of prohibiting and introducing restrictions in this area with the use of authoritative methods of state action gives rise to research that exposes the essence of the authorities’ fears of a complete opening of access to weapons. The administrators, referring to the principle of trust in the authorities, are approaching the features of an authoritarian approach to maintaining power, which is not to be hampered by the possession of weapons by citizens. Completely free access to ﬁrearms is not characteristic to those forms of government in which there is no trust in state’s citizens, nor conﬁdence in government’s position, susceptible to possible changes. In this regard, the basic rules governing access to ﬁrearms were presented, both in substantive law and in the rules of administrative procedure, with particular emphasis on the principle of raising trust in public authorities. It was also important to analyze the origins of the administrative power with an indication of the characteristic elements of the police state and their impact on the visions of access to ﬁrearms in the rule of law. Such a structure of the study made it possible to try to deﬁne the relationship between the trust of the authorities in their citizens and the trust of those administered to the authorities against the background of broadly understood security in the ﬁeld of access to ﬁrearms.
Keywords: bezpieczeństwo; władztwo publiczne; autorytaryzm; broń palna; zasada zaufania obywateli do państwa; kontrola